Hepatocyte ELOVL Fatty Acid Elongase 6 Determines Ceramide Acyl‐Chain Length and Hepatic Insulin Sensitivity in Mice. Issue 5 (7th February 2020) - Matsuzaka, Takashi; Kuba, Motoko; Koyasu, Saori; Yamamoto, Yuta; Motomura, Kaori; Arulmozhiraja, Sundaram; Ohno, Hiroshi; Sharma, Rahul; Shimura, Takuya; Okajima, Yuka; Han, Song‐iee; Aita, Yuichi; et al.
Abstract : Background and Aims: Dysfunctional hepatic lipid metabolism is a cause of nonalcoholic fatty liver disease (NAFLD), the most common chronic liver disorder worldwide, and is closely associated with insulin resistance and type 2 diabetes. ELOVL fatty acid elongase 6 (Elovl6) is responsible for converting C16 saturated and monounsaturated fatty acids (FAs) into C18 species. We have previously shown that Elovl6 contributes to obesity‐induced insulin resistance by modifying hepatic C16/C18‐related FA composition. Approach and Results: To define the precise molecular mechanism by which hepatic Elovl6 affects energy homeostasis and metabolic disease, we generated liver‐specific Elovl6 knockout (LKO) mice. Unexpectedly, LKO mice were not protected from high‐fat diet–induced insulin resistance. Instead, LKO mice exhibited higher insulin sensitivity than controls when consuming a high‐sucrose diet (HSD), which induces lipogenesis. Hepatic patatin‐like phospholipase domain‐containing protein 3 (Pnpla3) expression was down‐regulated in LKO mice, and adenoviral Pnpla3 restoration reversed the enhancement in insulin sensitivity in HSD‐fed LKO mice. Lipidomic analyses showed that the hepatic ceramide(d18:1/18:0) content was lower in LKO mice, which may explain the effect on insulin sensitivity. Ceramide(d18:1/18:0) enhances protein phosphatase 2A (PP2A) activity by interfering with the binding of PP2A to inhibitor 2 of PP2A, leading to Akt dephosphorylation. Its production involves the formation of an Elovl6–ceramide synthase 4 (CerS4) complex in the endoplasmic reticulum and a Pnpla3–CerS4 complex on lipid droplets. Consistent with this, liver‐specific Elovl6 deletion in ob/ob mice reduced both hepatic ceramide(d18:1/18:0) and PP2A activity and ameliorated insulin resistance. Conclusions: Our study demonstrates the key role of hepatic Elovl6 in the regulation of the acyl‐chain composition of ceramide and that C18:0‐ceramide is a potent regulator of hepatic insulin signaling linked to Pnpla3‐mediated NAFLD.